Analysis Of Law Number 28 Of 2014 Copyright On Plagiarism Test Among Universities On Legal Protection Of Scientific Papers - Purba, Novayani; Ramadani, Ramadani (UNIVERSITAS PAKUAN, 2022)
Plagiarism is often the most frequently faced thing by all universities, especially among final students who make scientific work. Law Number 28 of 2014 concerning Copyright itself states that scientific work is the object of protection from the law, In this study the author uses a statutory approach and a concept approach because it is considered relevant to the type of author's research which is normative juridical. The results showed that in the analysis of Law Number 28 of 2014 concerning Copyright against plagiarism tests among universities themselves is an effort to protect the copyright of the author. However, plagiarism testing itself is only an effort to reduce the chances of plagiarism, not to overcome and eradicate plagiarism as a crime of copyright infringement. The plagiarism test itself is the minimum form of effort in overcoming copyright infringement committed among universities. Legal protection against plagiarism among universities itself is not only carried out by plagiarism tests alone. Copyright infringement with plagiarism if only punished by a delay in the trial is considered not too meaningful. Eligibelization is a program from Kemenristekdikti as an effort to protect law against copyright infringement. However, this plagiarism test according to Law Number 28 of 2014 concerning Copyright has still not been able to overcome legal protection from copyright infringement. Eligibleization is an ideal form of legal protection among universities in reducing the number of copyright violations that occur in plagiarism of student scientific works.